ANALISIS PENGARUH RETURN ON ASSET (ROA), FINANCING TO DEPOSIT RATIO (FDR), DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP BAGI HASIL DEPOSITO MUDHARABAH (Pada Bank Umum Syariah di Indonesia yang terdaftar di OJK Tahun 2015-2018) - Wulandari, Retno; Ciptaningsih, Rokhmah Agus (JURNAL EKONOMI, 2022)
This study aims to determine: the effect of Return On Asset (ROA), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR) on Profit sharing mudharabah deposits The population of this study is the Islamic commercial banks in the 2015-2018 period. Determination of the sample using the purposive sampling method. The type of data used in secondary. The data analysis method used is multiple linear regression analysis. The result of this study indicate that: Return On Asset (ROA) does not affect profit sharing mudharabah deposits, Financing to Deposit Ratio (FDR) affect profit sharing mudharabah deposits, Capital Adequacy Ratio (CAR) does not affect profit sharing mudharabah deposits. The following suggestions are given: 1. Research object can be expanded, 2.This research can be an additional reference for the campus literature, 3. Islamic commercial banks are advised to pay attention to Return On Asset (ROA), Financing to Deposit Ratio (FDR), Capital Adequancy Ratio (CAR).